Guidance for microbial occupational exposure assessment in sawmills - Dias, Marta (2022)
The number of deaths attributed to occupational risks is projected to be around 1.2 million per year (statistics from 2015). The Commission's Health Emergency Preparedness and Response Authority (HERA) presented a priority list of top-3 health threats that require coordination of measures: pathogens with high pandemic potential; chemical, biological, radiological, and nuclear threats; threats resulting from antimicrobial resistance. In all European countries employers are obliged by regulation to assess and prevent exposure to occupational risks (Directive 89/391/EEC). Directive 2000/54/EC of the European Parliament and the Council of September 18, 2000, sets the rules regarding risk assessment if exposure to biological agents cannot be avoided (2000/54/EC, 2000). Sawmill workers may be exposed to allergenic, carcinogenic, and immunotoxic agents, which include wood derivatives as well as microorganisms that grow on wood and their metabolites, all of which are known to be potential health-harming agents. Wood dust is a complex mixture classified as a Group 1 carcinogen by the International Agency for Research on Cancer (IARC). This study aims to establish a guideline that allows a proper and complete exposure assessment in this specific occupational setting.